2019
DOI: 10.1111/cmi.13041
|View full text |Cite
|
Sign up to set email alerts
|

FgAP‐2 complex is essential for pathogenicity and polarised growth and regulates the apical localisation of membrane lipid flippases inFusarium graminearum

Abstract: AP-2 complex is widely distributed in eukaryotes in the form of heterotetramer that functions in the uptake of membrane proteins during mammalian/plant clathrin-mediated endocytosis. However, its biological function remains mysterious in pathogenic fungi. In this study, the wheat scab fungus, Fusarium graminearum, was used to characterise the biological function of the AP-2 complex. Our study shows that FgAP-2 complex plays a critical role in the maintenance of hyphal polarity.Lack of any subunit (FgAP2 α , Fg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 90 publications
(120 reference statements)
3
23
0
Order By: Relevance
“…Of these, each subgroup contains one F. graminearum ortholog except subgroup 3, which has the two FgDnfC members, suggesting that the FgDNFC gene has undergone duplication relative to its yeast homolog. To investigate the function of the five flippase genes in F. graminearum we used a homologous recombination strategy to generate their respective gene deletion mutants, except for FgDNFB , which has been generated from our previous study (Zhang et al ., 2019). The resulting hygromycin‐resistant transformants were screened by PCR (Table ) and Southern blot (Figure b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, each subgroup contains one F. graminearum ortholog except subgroup 3, which has the two FgDnfC members, suggesting that the FgDNFC gene has undergone duplication relative to its yeast homolog. To investigate the function of the five flippase genes in F. graminearum we used a homologous recombination strategy to generate their respective gene deletion mutants, except for FgDNFB , which has been generated from our previous study (Zhang et al ., 2019). The resulting hygromycin‐resistant transformants were screened by PCR (Table ) and Southern blot (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…In the rice blast fungus Magnaporthe oryzae , the biological functions of two flippases, MoPde1 and MoApt2, have been characterized, and both proteins are involved in fungal virulence (Balhadere and Talbot, 2001; Gilbert et al ., 2006). In F. graminearum recent studies identified FgDnfB and FgNeo1 (FgDnfD homologs) as flippases, and FgDnfB plays a minor role in fungal vegetative growth, polarity maintenance, and conidiation (Zhang et al ., 2019), while FgNeo1 is important for asexual/sexual developments and virulence in F. graminearum (Li et al ., 2019), but the remaining family proteins remain unknown. In addition, the roles of flippases in the biosynthesis of secondary metabolites have not been established in filamentous fungi.…”
Section: Introductionmentioning
confidence: 99%
“…However, FgPAL1 is not essential for polarity establishment or maintenance because the localization of FgSpa2 to hyphal tips was not affected in the Fgpal1 mutant. Recently, components of the FgAP-2 complex that functions as a cargo-specific adaptor for endocytosis have been reported to localize to the subapical collar in F. graminearum (Zhang et al, 2019). Therefore, it is important to determine the co-localization and possible functional relationship between FgPal1 and the FgAP-2 complex in endocytosis at the collar region of hyphal tips.…”
Section: Discussionmentioning
confidence: 99%
“…The H1-GFP construct (Luo et al, 2014) was transformed into the wild-type strain PH-1 and the Fgpal1 mutant to observe nuclei. The FgSpa2-GFP construct was generated by yeast gap repair as described (Bruno et al, 2004;Zhou et al, 2010) and transformed into the wild-type strain PH-1 and the Fgpal1 mutant to observe the polarisome (Zhang et al, 2019). Cell wall and septa were visualized by staining conidia or hyphae with 10 μg/ml −1 CFW for 2 min and observed with an Olympus BX-53 microscope as described (Luo et al, 2014;Li et al, 2015) Generation of the LifeAct-RFP FgPAL1-GFP transformant The LifeAct fragment consisting of the first 17 aa residues of yeast actin-binding protein Abp140 is an F-actin marker in eukaryotes (Lopata et al, 2018).…”
Section: Generation Of the Fgpal1 Deletion Mutant And Complemented Trmentioning
confidence: 99%
See 1 more Smart Citation